Dexamethasone exposure in normal‐weight and obese hospitalized COVID‐19 patients: An observational exploratory trial. Issue 7 (15th June 2022) - Abouir, Kenza; Gosselin, Pauline; Guerrier, Stéphane; Daali, Youssef; Desmeules, Jules; Grosgurin, Olivier; Reny, Jean‐Luc; Samer, Caroline; Calmy, Alexandra; Ing Lorenzini, Kuntheavy Roseline
Abstract: During the latest pandemic, the RECOVERY study showed the benefits of dexamethasone (DEX) use in COVID‐19 patients. Obesity has been proven to be an independent risk factor for severe forms of infection, but little information is available in the literature regarding DEX dose adjustment according to body weight. We conducted a prospective, observational, exploratory study at Geneva University Hospitals to assess the impact of weight on DEX pharmacokinetics (PK) in normal‐weight versus obese COVID‐19 hospitalized patients. Two groups of patients were enrolled: normal‐weight and obese (body mass index [BMI] 18.5–25 and >30 kg/m 2, respectively). All patients received the standard of care therapy of 6 mg DEX orally. Blood samples were collected, and DEX concentrations were measured. The mean DEX AUC0–8 and Cmax were lower in the obese compared to the normal‐weight group (572.02 ± 258.96 vs. 926.92 ± 552.12 ng h/ml and 138.67 ± 68.03 vs. 203.44 ± 126.30 ng/ml, respectively). A decrease in DEX AUC0–8 of 4% per additional BMI unit was observed, defining a significant relationship between weight and DEX AUC0–8 ( p = 0.004, 95% CI 2–7%). In women, irrespective of the BMI, DEX AUC0–8 increased by 214% in comparison to men ( p < 0.001, 95% CI 154–298%). Similarly, the mean Cmax increased by 205% in women ( p < 0.001, 95% CI 141–297%). Conversely, no significant difference between the obese and normal‐weight groups was observed for exploratory treatment outcomes, such as the length of hospitalization. BMI, weight, and gender significantly affected DEX AUC. We conclude that dose adjustment would be needed if the aim is to achieve the same exposures in normal‐weight and obese patients.